Beginning XNA 3.0 game programming from novice to professional - Lob(tilde)ao, Alexandre Santos; Safari eBooks (Berkeley, Calif. : Apress, 2009)
"This fast-paced introduction to XNA 3.0 and the C# language provides you with a quick-start guide to creating high-quality XNA games. You'll be introduced to the key concepts and ideas you need to know in a gradual fashion so that you master one concept before using it as a foundation for the next. Before long you will have the skills to create smooth, professional-looking results in a range of gaming genres. By the end of the book, you will have constructed several working games and have an excellent knowledge base from which to investigate more advanced techniques. This book is for anyone approaching XNA programming for the Xbox 360 for the first time, whether they have experience programming computer games or not"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Microsoft XNA (Computer file); Computer games -- Programming; Electronic books